2020
DOI: 10.1111/mec.15375
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection of digestive proteases in Daphnia: A mechanism for local adaptation to cyanobacterial protease inhibitors

Abstract: Due to the combined effects of global warming and eutrophication, the frequency of deleterious cyanobacterial blooms in freshwater ecosystems has increased. In line with this, local adaptation of the aquatic keystone herbivore Daphnia to cyanobacteria has received major attention. Besides microcystins, the most frequent cyanobacterial secondary metabolites in such blooms are protease inhibitors (PIs). Recently, it has been shown that a protease gene showed copy number variation between four D. magna population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Dietary protease inhibitors from M. aeruginosa strains have been shown to negatively affect Daphnia by hampering digestion and thus somatic growth rates (Rohrlack et al, 1999;Lürling, 2003;Schwarzenberger et al, 2010). However, it also has been demonstrated that Daphnia have specific means to cope with dietary protease inhibitors (Schwarzenberger et al, 2010(Schwarzenberger et al, , 2012(Schwarzenberger et al, , 2020Von Elert et al, 2012;, comprising physiological adaptations potentially resulting in population tolerance (Blom et al, 2006;Baumann and Jüttner, 2008;Schwarzenberger et al, 2017). Anabaenopeptins acting as carboxypeptidase inhibitors represent another group of harmful secondary metabolites produced by Planktothrix (Itou et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary protease inhibitors from M. aeruginosa strains have been shown to negatively affect Daphnia by hampering digestion and thus somatic growth rates (Rohrlack et al, 1999;Lürling, 2003;Schwarzenberger et al, 2010). However, it also has been demonstrated that Daphnia have specific means to cope with dietary protease inhibitors (Schwarzenberger et al, 2010(Schwarzenberger et al, , 2012(Schwarzenberger et al, , 2020Von Elert et al, 2012;, comprising physiological adaptations potentially resulting in population tolerance (Blom et al, 2006;Baumann and Jüttner, 2008;Schwarzenberger et al, 2017). Anabaenopeptins acting as carboxypeptidase inhibitors represent another group of harmful secondary metabolites produced by Planktothrix (Itou et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic resources are key components to deepening our understanding of the contributions of genetic background on strain-specific responses to toxic algal blooms and other environmental stressors. These resources can be used for understanding the transcriptomic responses to toxins ( Asselman et al 2012 ; Orsini et al 2016 ; Giraudo et al 2017 ), identifying sequence variants under positive selection across the genome ( Bourgeois et al 2017 ; Schwarzenberger et al 2020 ), and comparative analysis across other Daphnia species ( Ravindran et al 2019 ). In this way, these genomic resources provide a promising avenue for future research as the effects of urbanization and global climate change continue to exacerbate the severity of these toxic algal blooms over time ( Carpenter 2005 ; Schmale et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that the interclonal variability evident in several cladoceran genera can be attributed to differences in their metabolism and, as a result, their sensitivity to stressors (Barata et al 2001). Some studies (Chen et al 2005;Barrios et al 2017;Schwarzenberger et al 2020) also show that cyanobacterial extracts sometimes promote zooplankton growth because of the detoxification by enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacterial blooms are common in both natural and man‐made water bodies. Whereas most studies highlight the adverse effects of cyanotoxins, there are a few showing that zooplankton can develop resistance to cyanotoxins because of enzymatic activities (Chen et al 2005; Schwarzenberger et al 2020) or as a result of the ability of protists in decomposing cyanobacteria and increasing the available fatty acids (Luo et al 2015). Many urban lakes in Mexico City contain high densities of cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%